PENINGKATAN KAPASITAS APARATUR DAERAH DALAM PENYELENGGARAAN PELAYANAN PUBLIK - Drs. Desi Fernanda (Pusjar SKPP Lembaga Administrasi Negara, 2006)
The main purpose of regional autonomy is delivering better, faster, cheaper and closer public services as well as improving public welfare. To adroitly provide high-quality public service, both government officials and community members need to comprehend the basic concept and scope of services, and the principles of performance measurement regarding deliverance of public service. Besides, philosophical grounds on why government should carry out public services tasks are really matter to be recognized. Based on such common understanding, this paper offers some strategies concerning capacity building for service provider, i.e. government apparatus. Keywords: pelayanan publik, kapasitas aparatur, desentralisasi.